Special Editorial: Open science and the Journal of Child Psychology & Psychiatry – next steps?. (28th May 2018) - Asarnow, Joan; Bloch, Michael H.; Brandeis, Daniel; Alexandra Burt, S.; Fearon, Pasco; Fombonne, Eric; Green, Jonathan; Gregory, Alice; Gunnar, Megan; Halperin, Jeff M.; Hollis, Chris; Jaffee, Sara; et al.
Abstract : The JCPP works at the cutting edge of clinical science to publish ground‐breaking research across the full range of topics in the field of child psychology and psychiatry. As JCPP editors, who are also active researchers in our own right, we are conscious of the threat posed to our field by what has come to be known as the reproducibility crisis ‐ the fact that many published findings, initially trumpeted as important developments in the field, cannot be replicated and are therefore likely to be spurious (Nature Human Behaviour, 1, 2017, 21). The JCPP is conscious of its responsibility to play its part in addressing this issue as best it can. The roots of the problem are complex and its causes multifaceted. As one part of its response, the JCPP embraces the principles of open science and encourage preregistration of study protocols. Furthermore, we are working towards implementing new systems to promote preregistration with the hope of increasing scientific transparency and accountability and reducing the risks of selective reporting and posthoc rationalisation of findings (Journal of Child Psychology & Psychiatry, 59, 2018, 1).